2013
DOI: 10.1186/1297-9716-44-11
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Psoroptes ovis infestation on ovine epidermal barrier function

Abstract: Sheep scab is an intensively pruritic, exudative and allergic dermatitis of sheep caused by the ectoparasitic mite Psoroptes ovis. The purpose of the present study was to investigate the effect of P. ovis infestation on different components of the ovine epidermal barrier within the first 24 hours post-infestation (hpi). To achieve this, the expression of epidermal differentiation complex (EDC) genes and epidermal barrier proteins, the nature and severity of epidermal pathology and transepidermal water loss (TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 53 publications
0
10
0
1
Order By: Relevance
“…In this study, no suppression of the transcription of EDC genes could be observed (results not shown), unlike data available in sheep. As a down-regulation of these genes in sheep skin is seen within 24 h after infection, it is possible that this was missed in this study [ 9 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, no suppression of the transcription of EDC genes could be observed (results not shown), unlike data available in sheep. As a down-regulation of these genes in sheep skin is seen within 24 h after infection, it is possible that this was missed in this study [ 9 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in vitro culture of peripheral blood mononuclear cells (PBMC) showed an increased reactivity to mitogens [ 5 8 ]. In general, microscopic examination of the skin from infested ruminants reveals an increased dermal thickness and a superficial, perivascular dermatitis characterised by a fast influx of lymphocytes (including γδ T-cells in sheep), macrophages, mast cells, neutrophils and eosinophils [ 9 12 ]. Previous work on sheep scab demonstrated an up-regulation of genes encoding for pro-inflammatory and pro-allergic mediators [interleukin (IL)-1, IL-8, IL-6] and molecules involved in extravasation of immune cells [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pre‐TEWL measurements for sheep skin in this study were similar to those reported by Stoeckli et al . () (Stoeckli et al ., ). Transepidermal water loss is not commonly measured in sheep skin, and although TEWL is a rather unreliable measure of skin integrity (Chilcott et al ., ), it can be useful clinically for pre‐ and post‐treatment comparisons (Hester et al ., ).…”
Section: Discussionmentioning
confidence: 99%